2 day workshop on understanding geo-natural disasters arising from earthquake, tsunami and volcanic activities in Southeast Asia and seismic design using Eurocode 8 - Ooi, Teik Aun, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/